2002
DOI: 10.3758/bf03194324
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warnings on false memories in young and older adults

Abstract: In the present experiments , we examined adult age differences in the ability to suppress false memories, using the Deese-Roediger-McDermott (DRM) paradigm (Deese, 1959;Roediger & McDermott, 1995). Participants studied lists of words (e.g., bed, rest, awake, etc.), each related to a nonpresented critical lure word (e.g., sleep). Typically, recognition tests reveal false alarms to critical lures at rates comparable to those for hits for studied words. In two experiments, separate groups of young and older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
151
6
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 41 publications
12
151
6
5
Order By: Relevance
“…Although substantial false alarm rates generally persist following warnings, they are usually significantly lower than those of unwarned controls (e.g., Gallo, Roberts, & Seamon, 1997;McDermott & Roediger, 1998). Although some evidence indicates that the warning must be delivered before encoding of the study lists for a reduction in false alarms to occur (e.g., Anastasi, Rhodes, & Burns, 2000;Neuschatz, Payne, Lampinen, & Toglia, 2001), other evidence suggests that a warning delivered between study and test can have a beneficial effect as well (e.g., Lane, Roussel, Starns, Villa, & Alonzo, 2008;McCabe & Smith, 2002;Starns et al, 2007). If, as the latter finding suggests, participants benefit from insight into the test design without having such knowledge at study, the use of this information, and the consequent decrease in critical false alarms, must be achievable via processes operating at test.…”
Section: Methodsmentioning
confidence: 96%
“…Although substantial false alarm rates generally persist following warnings, they are usually significantly lower than those of unwarned controls (e.g., Gallo, Roberts, & Seamon, 1997;McDermott & Roediger, 1998). Although some evidence indicates that the warning must be delivered before encoding of the study lists for a reduction in false alarms to occur (e.g., Anastasi, Rhodes, & Burns, 2000;Neuschatz, Payne, Lampinen, & Toglia, 2001), other evidence suggests that a warning delivered between study and test can have a beneficial effect as well (e.g., Lane, Roussel, Starns, Villa, & Alonzo, 2008;McCabe & Smith, 2002;Starns et al, 2007). If, as the latter finding suggests, participants benefit from insight into the test design without having such knowledge at study, the use of this information, and the consequent decrease in critical false alarms, must be achievable via processes operating at test.…”
Section: Methodsmentioning
confidence: 96%
“…Chambers and Zaragoza (2001), however, found that warnings helped subjects regardless of when they were delivered. In studies of the DRM effect, pre-encoding warnings robustly reduced the rate of false memories, whereas the efficacy of postencoding warnings depended on other variables (e.g., Gallo, Roediger, & McDermott, 2001;McCabe & Smith, 2002;Watson, McDermott, & Balota, 2004). Two studies of greatest relevance to the present research have also found mixed results: Landau and von Glahn (2004) found that subjects who received warnings about imagination exhibited a smaller inflation effect than those who received no warning; whereas a study from the communications literature (Kelly & Nace, 1994) revealed that warnings about the capabilities of digital editing software failed to reduce subjects' belief in news articles and photos from disreputable sources.…”
Section: Methodsmentioning
confidence: 99%
“…Tun et al (1998) observed that age-related diVerences decreased when all participants were encouraged, through task demands, to rely on a gist representation of the study list. McCabe and Smith (2002) have also shown that older adults can reduce false alarms to the critical lure if warned prior to the encoding session about the nature of the task and materials. This suggests that although older adults may typically rely on gist-based representations, under certain conditions they are able to access and use more specific information.…”
Section: O R R E C T E D P R O O F E False Memory and Flexible Remmentioning
confidence: 99%